The Effect of Applying Talking Stick Type Learning Model in Mufrodat Learning: Quasi Experimental Research on Junior High School - Habibah, Ihda Filzafatin; Abidin, Munirul (Jurnal Sustainable, 2023)
This study  aims to determine the  effect of  the application of the "Talking Stick"  type learning    model on improving  Mufrodat (Arabic Vocabulary) learning in  junior  high school students.  In this study,  researchers used research based on Quasi-Experimental  studies by dividing students  into two classes, namely the  experimental class  and  the control class.    This research is based on  several complex problems, namely Arabic learning  is still considered as one of  the difficult and boring subjects. The results  showed that  by using the  "Talking stick" type  of learning model,  mufrodat  learning  in students increased compared to  applying the conventional learning model  to generally.  With this research,  it is expected to be a motivation for educators  at  every  level of  education  to continue  and continue to  innovate in every application of learning  by  Models  that vary and adapt to the  technology of the era that exists today.